2022
DOI: 10.3390/atmos13111811
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Methane Emission and the Factors That Influence It, from Three Rice Varieties Commonly Cultivated in the State of Puducherry

Abstract: India being the world’s second largest cultivator of paddy, it is very important that the extent of the resulting methane emissions is estimated, and steps are taken to minimize these emissions. Peninsular India is a prime rice-producing region; however, no significant information is available on the contribution of this region to methane emissions, nor are there available studies that show the effect of cultivars, growth seasons, soil characteristics, etc., on methane emissions. As one of the attempts to cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Methane flux decreases after the flowering stage because the photosynthetic rate decreases after seed development, and the availability of assimilates for methane formation decreases (Wihardjaka and Sarwoto, 2015). Previous research has also shown similar results, with the highest methane fluxes observed during the vegetative and early reproductive phases (about 25 days after showing), followed by a decline during the flowering and maturity phases (Chandrasekaran et al, 2022).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Methane flux decreases after the flowering stage because the photosynthetic rate decreases after seed development, and the availability of assimilates for methane formation decreases (Wihardjaka and Sarwoto, 2015). Previous research has also shown similar results, with the highest methane fluxes observed during the vegetative and early reproductive phases (about 25 days after showing), followed by a decline during the flowering and maturity phases (Chandrasekaran et al, 2022).…”
Section: Discussionsupporting
confidence: 65%
“…Additionally, previous research has shown that rice variety differences significantly affect greenhouse gas emissions. Shortduration and water-efficient rice varieties can reduce CH 4 emission fluxes under low-water irrigation conditions (Chandrasekaran et al, 2022). In this study, the Way Apo rice variety produced lower CH 4 emissions compared to Inpari 32 under the P1, P3, and P4 fertilizer variations.…”
mentioning
confidence: 61%
“…Seasonal temperature variation strongly affects methane flux during the plantation period in various rice field locations in Japan (Yagi & Minami, 1991). Similarly, Chandrasekaran et al (2022) reported that methane emissions increase linearly to the increase in soil temperature in India. Temperature affects methane emissions through anaerobic digestion reactors, which are done by mesophilic (20~42°C) or thermophilic (42~75°C) organisms such as methanogens (Parawira, 2004).…”
Section: Climate/weathermentioning
confidence: 92%
“…The next factor that influences methane production is temperature because temperature changes in the soil would affect the methanogens (Schulz et al, 1996;Chandrasekaran et al, 2022). Seasonal temperature variation strongly affects methane flux during the plantation period in various rice field locations in Japan (Yagi & Minami, 1991).…”
Section: Climate/weathermentioning
confidence: 99%
“…Studies have reported that CO 2 , CH 4 , and N 2 O are the topmost three natural greenhouse gases, responsible for 64%, 17%, and 6% of the total radiative forcing (Myhre et al 2013;Tran et al 2017). CO 2 is often given the most attention due to the contributions from human activity to its rising levels; however, CH 4 and N 2 O have about 34 and 300 times higher global warming potential, respectively, than CO 2 (Gri s et al 2017; Chandrasekaran et al 2022).…”
Section: Introductionmentioning
confidence: 99%